Maize Ethylene Response Factor ZmERF061 Is Required for Resistance to Exserohilum turcicum - Zang, Zhenyuan; Wang, Zhen; Zhao, Fuxing; Yang, Wei; Ci, Jiabin; Ren, Xuejiao; Jiang, Liangyu; Yang, Weiguang (Frontiers in Plant Science, 2021)
Plants have evolved a series of sophisticated defense mechanisms to help them from harm. Ethylene response factor (ERF) plays pivotal roles in plant immune reactions, however its underlying mechanism in maize with a defensive function to E. turcicum remains poorly understood. Here, we we isolated and characterized a novel ERF transcription factor, designated ZmERF061, from maize. Phylogenetic analysis revealed that ZmERF061 is a member of B3 group in ERF family. qRT-PCR assays showed that the expression of ZmERF061 is significantly induced by E. turcicum inoculation and by hormone treatment with SA and MeJA. ZmERF061 was proved to function as a nucleus-localized transcription activator and specifically bind to the GCC-box element. zmerf061 mutant lines resulted in enhanced susceptibility to E. turcicum via decreasing the expression of ZmPR10.1 and ZmPR10.2 and the activity of antioxidant defense system. zmerf061 mutant lines increased the expression of the SA signaling-related gene ZmPR1a and decreased the expression of the JA signaling-related gene ZmLox1 after infection with E. turcicum. In addition, ZmERF061 could interact with ZmMPK6-1. These results suggested that ZmERF061 plays an important role in response to E. turcicum and may be useful in genetic engineering breeding.